Corporate Sustainability and the Sustainable Development Goals: Respect for Civil Rights in Business - Bester, Tequila V. (The Indonesian Forestry Certification Cooperation, 2021)
This study explores the relationship between the sustainable development goals (SDGs) and corporate sustainability (CS) through a business and human rights (BHR) lens. It affirms established guidance that companies must show respect for human rights. As a new factor, the study considers how corporations recognise civil rights. The authors examine annual reports and other material of five Fortune Global 500 multinational enterprises (MNEs) from five sectors to establish their relationship with UNGPs, SDGs and civil rights. They also review policies and reports to determine the MNEs management system(s) (MS) and system certifications. While the sample is too small to make correlations, the authors find that the sample MNEs do recognise civil rights under the guise of human rights. They appear to address civil rights issues that trend globally, not necessarily the problems that occur on the national or local level. Although the sample countries contribute to SDGs, this engagement seems connected to the MNEs business strategy. Their SDGs involvement can change from one fiscal year to the next, depending on the business strategy. In the study, the authors focus on corporate management systems (MSs) and seek to identify elements of a good MS. They recommend that companies expose their MSs to audit and certification processes to ensure that respect for civil and human rights are embedded in their systems.